Assessment of safety performance level on simple urban residential building: Case study at Bogor City Indonesia - M., Lutfi; H., Arien; M., Hendrawati; Putra Jaya, Ramadhansyah; Noram Irwan, Ramli (IOP Publishing, 2020)
Simple urban residential building must meet the technical requirements set forth in the building and structure law number 28 of 2002. In the city of Bogor, especially in the densely populated village of Kayumanis, there are areas that have the potential of landslides. In that area, there are some houses that have been damaged by the movement of land and landslides that can threaten the safety of its inhabitants. Therefore they need to stay aware about potential collapse of several parts of house structures, and then understand how to evacuate to safer area, outside of the house after the incident was stopped. Based on these conditions, it is necessary to evaluate buildings in accordance with FEMA on the safety level of buildings. The structure and modeling analysis using SAP 2000-V10 and Indonesia Standard. Specification of simple urban residential building using the reinforced concrete material with the quality of concrete (fc') 17 MPa, 15x15 cm column dimension, 15x18 cm beam dimension and 4D12 BJTP main reinforcement, and shear reinforcement D8-20. The results of the analysis of urban residential building structures shown in 3D form, obtained values for column structure elements almost close to failure are marked with orange color, while for the element of the beam structure is declared safe marked with green color. From result of modeling analysis referring to FEMA 356 obtained value C0 = 1.0; C1 = 1.378; C2 = 1.0; C3 = 1.0; Sa = 1.011; and Te = 0.2206, which states the value of the displacement target is 0.02 m which is categorized to be at 'The Life Safety' (LS) performance level. This means that if there is a movement of land, the structure of the house is declared stable and has adequate service capacity and damage non-structural part is still controlled.